RESILIENCE, WORSHIP, AND AI: DRIVERS OF ACADEMIC TIMELINESS FOR SUSTAINABLE EDUCATION - Ambarwati, Ambarwati; Hidayati, Suci; Rohmawati, Yuli Nur; Izzah, Khoirotul; Anggarini, Ida Fitri (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study focuses on evaluating university students’ ability to complete academic assignments accurately and on time. Timeliness in completing tasks may be influenced by both external and internal factors. Resilience, religious habituation, and technological utilization are among the variables that can shape individual behavior, particularly in the digital generation. Purpose: The aim of this research is to examine the extent to which resilience, the routine practice of congregational prayer, and the use of Artefact Intelligence (AI) affect students’ punctuality in completing academic assignments. Method: The research sample consisted of 100 postgraduate students from five study programs at Universitas Islam Negeri Maulana Malik Ibrahim Malang, all in their second semester. Data were collected over a three-week period using a Likert-scale questionnaire (1–5). Result: Findings indicate that resilience, the frequency of congregational prayer, and AI utilization collectively have a significant influence of 58.3% on assignment timeliness, while the remaining 31.7% is attributed to other factors not examined in this study. Conclusion: Further analysis shows that congregational prayer and AI usage each have significant effects, with p-values of 0.005 and 0.001 at the 5% confidence level, respectively, whereas resilience does not significantly impact timeliness. Implications: This lack of significance may be due to reduced perseverance among Generation Z students, many of whom lack strong motivation, spend considerable time in leisure, and have limited engagement in social environments